Management of patent ductus arteriosus in premature infants. - A. Obolonskyi; V. Snisar; D. Surkov; O. Obolonska; O. Kapustina; K. Dereza (Medičnì Perspektivi)
Closure of hemodynamically significant patent ductus arterios (HSPDA)  is one of the most important questions in modern neonatal intensive care, especially for preterm babies. Long-term functioning of the hemodynamically significant  arterial duct leads to a large number of complications in premature babies, such as: bronchopulmonary dysplasia, periventricular leucomalacia, intraventricular hemorrhage, retinopathy of the premature. To prevent all these complications, the PDA should be closed pharmacologically or surgically as soon as possible without any hesitation. COX inhibitors are commonly used nowa days. Ibuprofen and indomethacin show the equal efficacy and no significant adverse events. But some patients still need surgical treatment. The aim of the study was to determine the feasibility, effectiveness and safety of using various volumes of infusion in combination with COX inhibitors and to determine its effect on the timing of the closure of PDA. 91 premature infants with a gestational age of 26-31 weeks with manifestations of respiratory distress syndrome and НSPDA were studied retrospectively. Premies were divided into 2 groups. Research groups were representative as to gestational age, gender, and weight (1205.0±435.0 g). Therapy for PDA closure included the use of various volumes of restrictive or liberal infusion therapy (from 50 to 100 ml/kg/day) and COX inhibitors (indomethacin, ibuprofen). The volume of infusion therapy was limited in the first group. Preemies received 53.5±6.4 ml/kg/day on DOL1 and 2. From the third day urine excretion increased and the volume of infusion therapy also raised to 63.6±5.6 ml/kg/day, and on day 5 – to 89.7±6.8 ml/kg/day. In the second group there was no strict limitation of the volume of infusion therapy (especially in the first 5 days). Delayed period of PDA closure (on average from 14.55±0.56 DOL) was associated with absence of limitation of the infusion volume. In the first group, volume of infusion therapy was restricted in the first 5 days, and the closure of the ductus arteriosus occurred extremely early (on 2.35±0.48 DOL). COX inhibitors were prescribed according to the standard scheme: in the first 3 days indomethacin was administered orally in doses of 0.2/0.1/0.1 mg/kg/day. If the premature baby had symptoms of intestinal paresis ( this restricted oral administration of indomethacin), ibuprofen was prescribed in a three-day course in doses of 10/5/5 mg/kg/day intravenously or 20/10/10 mg/kg/day in rectal form. In all  groups, standard PDA closure therapy was used. In the more remote periods (14 and 28 days), there was no fundamental difference in the volume of infusion in all groups. For early PDA closure limitation of infusion therapy in the first 3-5 days in combination with COX is principle.